CD180 Ligation Inhibits TLR7- and TLR9-Mediated Activation of Macrophages and Dendritic Cells Through the Lyn-SHP-1/2 Axis in Murine Lupus - Yang, Yonghong; Wang, Cuiling; Cheng, Panpan; Zhang, Xiaobei; Li, Xuehui; Hu, Yuan; Xu, Feihong; Hong, Feng; Dong, Guanjun; Xiong, Huabao (Frontiers in Immunology, 2018)
Activation of TLR7 and TLR9 by endogenous RNA- or DNA-containing ligands, respectively, can lead to hyper-activation of immune cells, including macrophages and DCs, subsequently contributes to the pathogenesis of SLE. CD180, a TLR-like protein, has been shown to participate in development and activation of immune cells. Our previous study and others have reported that CD180-negative B cells are dramatically increased in SLE patients and responsible for the production of auto-antibodies. However, the mode of CD180 expression on macrophages and DCs in SLE remains unclear and the role of CD180 on regulating TLR7- and TLR9-mediated activation of macrophages and DCs are largely unknown. In the present study, we found that the percentages of CD180-negative macrophages and DCs were both increased in SLE patients and lupus-prone MRL/lpr mice compared with healthy donors and wild-type mice, respectively. Notably, ligation of CD180 significantly inhibited the activation of TLR7 and TLR9 signaling pathways in macrophages and DCs through the Lyn-SHP-1/2 axis. What’s more, injection of anti-CD180 Ab could markedly ameliorate the lupus-symptoms of imiquimod-treated mice and lupus-prone MRL/lpr mice through inhibiting the activation of macrophages and DCs. Collectively, our results highlight a critical role of CD180 in regulating TLR7- and TLR9-mediated activation of macrophages and DCs, hinting that CD180 can be regarded as a potential therapeutic target for SLE treatment.